DISGORGEMENT (FUND): A NEW ERA OF INVESTOR PROTECTION IN THE CAPITAL MARKET - Nikmah Mentari (JIL : Journal of Indonesian Law, 2021)
Violations in the capital market often harm investors. Despite administrative and criminal sanctions, the losses suffered by investors are not recoverable. If an investor wants to make a collection or claim for compensation, they must go through a civil suit that takes time, cost and energy. This causes a crisis of confidence in investment in the capital market due to the lack of legal protection. Therefore, the return of profits received illegally must be returned which is called disgorgement. Disgorgement is a legal protection for investors in the capital market that significantly impacts the return of compensation. This paper uses normative legal research with a statutory and conceptual approach. The results obtained that the importance of legal protection for investors will affect the existence of the capital market itself. Through disgorgement, investors will feel protected by their interests, thus creating justice. The existence of justice for investors as victims is the goal of legal protection itself.